Real-Time School Violence Reporting Process Using Smart Bands - Cheol Park, Won; Rack Park, Koo; Suk Chung, Young; Young Jeong, Jin (International Journal of Engineering and Technology, 2018)
Background/Objectives: The number of school violence victims has not gone down in the country. Moreover, there are no adequate measures against violence committed in a blind spot that the CCTV coverage has, unnoticed by the public eye. Therefore, there is a need to devise an alternative system for preventing school violence committed in the blind spot.Methods/Statistical analysis: With default settings, an application that transmits location information based on the Bluetooth communication of smart bands and smartphones is installed. In the application, the number of people to whom a user wants to transmit location information is stored. If the user click the button of the smart band, the location information transmission application of the smartphone receives the signal with the Bluetooth communication. The real-time location information of the user is transmitted to the list stored in the location information transmission application by SMS text message. The transmitted location information is stored in the database in the form of X and Y coordinates.Findings: This paper proposes a real-time location information transmission process that can prepare for violence by transmitting real-time location information and calling for help in the case of violence committed in a blind spot outside the CCTV coverage range. The location information notification application has been widely used. However, since it requires manual operation, it is difficult to efficiently transmit location information in actual situations. In this regard, it is expected that the proposed process can help to escape from the violence situation effectively by transmitting the location information in real-time situations.Improvements/Applications: For future work, there is a need for continuous research to collect information on blind spots as big data for collecting information on places where school violence occurs frequently, and thus to prevent violent crimes that occur in areas other than the school.Â